Making an Onboard Reference Map From MRO/CTX Imagery for Mars 2020 Lander Vision System. Issue 8 (11th August 2021) - Cheng, Yang; Ansar, Adnan; Johnson, Andrew
Abstract: The Mars 2020 rover, Perseverance, landed in Jezero crater (18.4663°N, 77.4298°E) on February 18, 2021 to collect samples from Mars that could be returned to Earth by a future Mars Sample Return campaign. While providing a rich sampling opportunity, Jezero also contains numerous landing hazards including scarps, canyons, mesas, dune fields, rock fields, and smaller craters. The Mars 2020 onboard inertial navigation system, which is the same as that used by the Mars Science Laboratory (MSL), only provides a very coarse inertially propagated position, which can have error as large as 3.2 km. The Lander Vision System (LVS) was added to Mars 2020 to reduce this position knowledge error to less than 40 m with respect to an on‐board reference map of the landing area. LVS uses a reference map on board to compare with the descent images for lander localization during the terminal stage of Entry, Descent and Landing (EDL). Because the reference map is used directly during EDL, it is critical that it have as little spatial and photometric error as possible. Photometrically, it should resemble as much as possible the real descent images to allow reliable terrain matching. Spatially, it should match as faithfully as possible the real, underlying terrain and contribute minimal error to the final localization solution. On February 18, 2021, the LVS reference map passed its ultimate test. The LVS system executed Terrain Relative Navigation (TRN) flawlessly based on the LVS reference map. In addition to its use for TRN, the local hazard map is also registered to the LVS reference map so that the safe target selection (STS) system can select a safe and reachable landing site. The final error between the site targeted by the STS system and the real landing site is estimated at only 5 m. The exceptional performance of LVS indicates that the reference map met mission requirements with comfortable margin. LVS on Mars 2020 represents the first ever use of a reference map during spacecraft EDL. This breakthrough will have profound implications for future lander missions and the scope of scientific inquiry they are able to address. In this paper, we will describe the necessary precursor steps to building the Jezero Crater LVS map, including the methodology to dejitter Context Imager (CTX) images, improve the CTX sensor model, as well as the process used to validate the LVS map accuracy. Key Points: The Lander Vision System used for precision landing by the Mars 2020 mission required unprecedented fidelity in the onboard reference map This study describes methods used to generate an onboard reference map with the required fidelity This study describes methods used to validate the onboard reference map